GE_GERICHTE P/6630/2011 vom 19. Januar 2012 - GE Cour de justice (2012)
; DÉFAUT(CONTUMACE) ; CONDITION DE RECEVABILITÉ ; APPEL(CPP) ; ORDONNANCE DE CONDAMNATION | CPP.368; CPP.399.3; C`PP.356.4; CPP.371.1